Microbial profile of ultrasonic cleaner water - Esther Wijaya; Mirza Indrajanti; Seri Nila; Jesslyn Sharon; J. FR Sulistyorini (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
It is necessary to clean glasses regularly. Glasses are often dirty due to attached dusts and contaminated microbe. Ultrasonic cleaner is often used effectively to clean the glasses. Therefore, the ultrasonic cleaner water contains contaminated microbe from glasses. This study aimed to identify bacteria and fungi yeast in the used ultrasonic cleaner water. For this study, glasses were cleaned with ultrasonic cleaner. Then, its water is inoculated at 3M Petrifilm for Escherichia coli, Staphylococcus aureus, and Candida albicans. The results showed that the most frequent Staphylococcus aureus and Candida albicans in the ultrasonic cleaner water. Escherichia coli was not often found. Since both of microbe, S. aureus and C.albicans are flora normal of the skin, it can be concluded that glasses are contaminated with these flora normal of the skin